1990
DOI: 10.1111/j.1432-1033.1990.tb15649.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure and inhibition of protein synthesis in eukaryotic cell‐free system of a novel thionin, γ‐hordothionin, from barley endosperm

Abstract: A new sulfur-rich and basic polypeptide, designated as y-hordothionin, has been isolated from barley endosperm by a semi-preparative purification consisting of extraction with a volatile salt solution followed by highperformance liquid chromatography using a reversed-phase C4 column. The isolated polypeptide was found to be homogeneous by micro-two-dimensional gel electrophoresis in the presence of sodium dodecyl sulfate. The complete primary structure of y-hordothionin was determined by automatic degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
154
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(159 citation statements)
references
References 29 publications
1
154
2
Order By: Relevance
“…NaD1, PhD1, and PhD2 and the floral defensins, FST from cultivated tobacco (Gu et al, 1992) and TPP3 from tomato (Milligan and Gasser, 1995) all have a predicted C-terminal domain of 27 to 33 amino acids in addition to the defensin domain. In contrast, the floral defensins PPT from petunia (Karunanandaa et al, 1994) and TGAS118 from tomato (van den Heuvel et al, 2001) lack this C-terminal domain, as do the seed defensins from radish (Rs-AFP2; [Terras et al, 1995], alfalfa [alfAFP; Gao et al, 2000]), and wheat (␥1-P; Colilla et al, 1990;Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NaD1, PhD1, and PhD2 and the floral defensins, FST from cultivated tobacco (Gu et al, 1992) and TPP3 from tomato (Milligan and Gasser, 1995) all have a predicted C-terminal domain of 27 to 33 amino acids in addition to the defensin domain. In contrast, the floral defensins PPT from petunia (Karunanandaa et al, 1994) and TGAS118 from tomato (van den Heuvel et al, 2001) lack this C-terminal domain, as do the seed defensins from radish (Rs-AFP2; [Terras et al, 1995], alfalfa [alfAFP; Gao et al, 2000]), and wheat (␥1-P; Colilla et al, 1990;Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…The first plant defensins were isolated from wheat (Triticum aestivum) and barley (Hordeum vulgare), and were initially classified as a subgroup of the thionin family called the ␥-thionins (Colilla et al, 1990;Mendez et al, 1990). Subsequent identification of other ␥-thionin-like proteins in other plant families, together with structural information, revealed striking differences between ␥-thionins and classical thionins (Bruix et al, 1993;Terras et al, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first plant defensins were isolated from wheat and barley seeds 214 . Most plant defensins are seed specific, but are also expressed in vegetative tissues.…”
Section: Defensins (γ-Hordothionins) (Pr-12)mentioning
confidence: 99%
“…Loop 2 has been shown to be important for interaction and enzyme inhibition; it may prevent the entrance of the substrate by insertion into the active site of TMA. Moreover, it was found that positively charged residues in loops 1 and 2 may be important for interaction with α-amylases 192,214 . The ability of defensins to chelate calcium 51 may cause enzyme inhibition by destabilizing the enzyme molecule 258 .…”
Section: Defensins (γ-Hordothionins) (Pr-12)mentioning
confidence: 99%